Qudamah Ibn Ja’far on Certain Aspects of Political Economy - Kallek, Cengiz (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Qudamah Ibn Ja’far on Certain Aspects of Political Economy